2019
DOI: 10.1038/s41598-019-43397-y
|View full text |Cite
|
Sign up to set email alerts
|

Atypical body movements during night in young children with autism spectrum disorder: a pilot study

Abstract: Children with autism spectrum disorder (ASD) reportedly suffer from sleep problems at a higher rate than typically developing (TD) children. Several previous studies have reported differences in sleep indices (e.g., sleep latency) in children with ASD. However, no previous studies have focused specifically on the time course of body movements. In the present study, we investigated the time course of body movements in young TD children and young children with ASD as well as the relationship between body movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Movement during sleep (Factor 1) originated from questions related to moving in bed and moving during sleep; regularity of sleep (Factor 2) from regularity of bedtime and wake time; sleep disturbances (Factor 3) from questions on sleeping less, trouble sleeping and nightmares; and sleep pressure (Factor 4) from questions on sleeping more, needing naps and waking up at different times. Sleep movement [55,56], regularity of sleep [57,58], sleep disturbances [20], and sleep pressure [59] were used in sleep research to evaluate sleep patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Movement during sleep (Factor 1) originated from questions related to moving in bed and moving during sleep; regularity of sleep (Factor 2) from regularity of bedtime and wake time; sleep disturbances (Factor 3) from questions on sleeping less, trouble sleeping and nightmares; and sleep pressure (Factor 4) from questions on sleeping more, needing naps and waking up at different times. Sleep movement [55,56], regularity of sleep [57,58], sleep disturbances [20], and sleep pressure [59] were used in sleep research to evaluate sleep patterns.…”
Section: Discussionmentioning
confidence: 99%
“… Behavior problems correlated significantly with sleep problems ( r = 0.597, p < 0.05) Social withdrawal and inappropriate speech variables were significantly correlated with sleep problems. 11 Naito et al (2019) 58 Japan Investigated the time course of body movements at night and their relationship with social ability. ASD (n=17), M (76.47%), aged 5–8 M =6.43 DSM V, ADOS Pilot Study.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier reports of some studies have described increased wake after sleep onset based on caregiver’s reports [ 8 ], PSG [ 71 , 72 , 73 ], and actigraphy [ 74 ], suggesting increased body movement after sleep onset in ASD. Use of the same dataset as that used for the present study revealed that the duration of body movements was longer in children with ASD over similar time periods to those examined for our study [ 46 ]. Considering these findings collectively, the behavior of increased body movement in ASD is characterized with regularity, specifically in the early and late stages of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Information related to participants, measurements, and preprocessing of actigraphy has been reported by Naito et al [ 46 ]. Participants in this cross-sectional study were 17 TD children with no reported behavioral or language problem and 17 children with ASD recruited from Kanazawa University and prefectural hospitals in Kanazawa or Toyama.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation